Diversity-oriented fluorescence library approaches for probe discovery and development - Vendrell, Marc; Lee, Jun-Seok; Chang, Young-Tae (ELSEVIER SCI LTD, 2010)
Diversity-oriented fluorescence library approaches have significantly accelerated the development of new sensors. By making use of combinatorial chemistry and high-throughput screening, they can circumvent our limitations in designing probes for particular recognition processes. Combinatorial chemists have proved how to derivatize fluorogenic scaffolds, tune their photophysical spectra and adjust their properties (from cell permeability to quantum yields) to generate libraries of potential sensors. Several platforms (in vitro assays, cell-based imaging) have also been optimized to screen these libraries in a high-throughput manner, and with the recent progress in image acquisition and analysis, their scope has been expanded toward more diverse and demanding biological systems. Supported by successful examples of fluorescent sensors for biomolecules, proteins, or even phenotypes, this review (together with a video abstract) stresses the important role that diversity-oriented approaches will continue to play in probe development in the near future.
Keywords: SOLID-PHASE SYNTHESIS; COMBINATORIAL DISCOVERY; PARALLEL SYNTHESIS; IMAGING PROBES; SENSORS; DYES; FLUOROPHORES; DERIVATIVES; CHEMOSENSORS